Binding of pea cytochrome f to the inner membrane of Escherichia coli requires the bacterial secA gene product. - Rothstein, S J (1985)
Various sequences from the 5' end of the pea chloroplast gene for cytochrome f have been fused in the correct reading frame with lacZ, and the cellular location of the hybrid polypeptides in Escherichia coli has been examined. Hybrid polypeptides containing N-terminal parts of cytochrome f are located in the cytoplasmic membrane of E. coli. Membrane localization is most efficient when the intact signal sequence of cytochrome f is present at the N-terminal end of the fusion proteins. Fusion within the signal sequence, so that the processing site is absent, reduces the efficiency of membrane binding. Membrane insertion of fusion proteins containing signal sequences is prevented in a temperature-sensitive secA strain at the nonpermissive temperature and the hybrid proteins accumulate in the cytoplasm. This indicates that specific recognition of the chloroplast signal sequence occurs in the bacterial secretory pathway.